Integration of Artificial Intelligence in Kurikulum Berbasis Cinta: Challenges and Ethics in Islamic Science Education - Dewі Wulansari; Saefudin Zuhri; Taqiyuddin Taqiyuddin; Didin Nurul Rosidin; Wahyudin Wahyudin (Eduvest - Journal of Universal Studies, 2026)
The integration of artificial intelligence (AI) in education has significantly transformed learning processes, including in Islamic education, where maintaining moral and spiritual values is essential. This study aims to explore the potential, challenges, and ethical implications of integrating AI into a Kurikulum Cinta that emphasizes compassion and empathy in Islamic science education. The research employs a qualitative approach through a systematic literature review, collecting data from relevant journals, books, and research reports. Data were analyzed using content analysis techniques to identify key themes related to AI integration, digital literacy challenges, and ethical considerations. The findings reveal that AI enhances learning effectiveness through personalized instruction, increased student engagement, and improved accessibility. However, significant challenges persist, particularly in teachers’ digital literacy, technical readiness, and concerns regarding data privacy and ethical use. The study also highlights that a Kurikulum Cinta can bridge the gap between technological advancement and spiritual values by integrating empathy and moral teachings into AI-supported learning environments. Ethical principles such as responsibility (amanah) and proper conduct (adab) must guide AI implementation. In conclusion, AI integration in Islamic education is promising but requires strategic planning, ethical guidelines, and continuous capacity building to ensure alignment with humanistic and spiritual objectives.